Implementasi Kurikulum Merdeka Belajar Pada Program Pendidikan Kesetaraan - Azka Nafiurrohmah; Ilyas Ilyas (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The "Merdeka Belajar" curriculum is a project-based learning curriculum aimed at developing the Pancasila student profile, focusing more on essential material and character development of the students. This study aims to identify and describe: 1) the implementation of the "Merdeka" curriculum, 2) the problems encountered, and 3) the efforts to overcome the problems faced in the implementation of the "Merdeka Belajar" curriculum in the equivalency education program for package C class X at PKBM Citra Ilmu, Semarang Regency. The research was conducted using a qualitative descriptive method, with informants including the PKBM manager, 2 tutors, and 2 learning residents. Data collection methods involved observation, interviews, and documentation. Data validity was tested using source and technique triangulation. Data analysis techniques included stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the "Merdeka Belajar" curriculum in the equivalency education program for package C class X has been quite good, starting from planning, implementation, to evaluation. The problems encountered in the implementation of the "Merdeka" curriculum include low participation from learning residents, suboptimal differentiation implementation, and inadequate facilities. Efforts made to address these problems include providing motivation to learning residents, conducting workshops and in-house training, and maximizing the existing facilities. This study explores the implementation of the "Merdeka" curriculum in the context of package C equivalency education, which has not been widely researched previously.